Armies of the young : child soldiers in war and terrorism - Rosen, David M., 1944- (Rutgers series in childhood studies., 2005)
Children have served as soldiers throughout history. They fought in the American Revolution, the Civil War, and in both world wars. They served as uniformed soldiers, camouflaged insurgents, and even suicide bombers. Indeed, the first U.S. soldier to be killed by hostile fire in the Afghanistan war was shot in ambush by a fourteen-year-old boy. Does this mean that child soldiers are aggressors? Or are they victims? It is a difficult question with no obvious answer, yet in recent years the acceptable answer among humanitarian organizations and contemporary scholars has been resoundingly the latter. These children are most often seen as especially hideous examples of adult criminal exploitation. In this provocative book, David M. Rosen argues that this response vastly oversimplifies the child soldier problem. Drawing on three dramatic examples-from Sierra Leone, Palestine, and Eastern Europe during the Holocaust-Rosen vividly illustrates this controversial view. In each case, he shows that children are not always passive victims, but often make the rational decision that not fighting is worse than fighting. With a critical eye to international law, Armies of the Young urges readers to reconsider the situation of child combatants in light of circumstance and history before adopting uninformed child protectionist views. In the process, Rosen paints a memorable and unsettling picture of the role of children in international conflicts.